Extraction of extracellular polymeric substances from dam lake fresh sediments derived from crystalline bedrock. (July 2021) - Le Guet, Thibaut; Camotti Bastos, Marilia; Robin, Valentin; Bourven, Isabelle; Guibaud, Gilles
Abstract: Extracellular polymeric substances (EPS) produced by microorganisms have a key role in the sedimentary compartment, e.g. promoting aggregation and biostabilisation of sediment particles and increasing chemical reactivity at the water/sediment interface. Therefore, proper extraction methods are needed to study this EPS matrix. In this work, nine extraction methods based on physical (centrifugation, sonication), chemical (sodium hydroxide, sodium pyrophosphate, sodium tetraborate), and both chemical and physical (cation exchange resins, i.e. CER) treatments and their combinations, as well as the solid:liquid ratio used for extraction, were compared based on the quantity and compositions of extracted EPS. The organic carbon extracted was quantified and the nature of biochemical macromolecules (proteins, polysaccharides, and humic-like compounds) was evaluated using colorimetric methods. The amount of ATP was used as an indicator of cell lysis and showed contamination with intracellular materials in EPS extracted with chemical methods. Moreover, chemical extraction presented a large quantity of impurities due to non-removal of reactant salts by ultracentrifugation. For the nine methods tested, humic-like substances represented the main fraction of the extracted EPS, but for chemical extraction, the presence of humic materials from the sediment organic fraction was due to non-specific extraction of the EPS fraction. Therefore, chemicals methods are not recommended to extract EPS from sediment. Despite their low extraction efficiency, physical methods and CER, i.e. 'soft' extraction methods, are preferred using a solid:liquid ratio 1:40. Highlights: Nine methods and three S/L ratios tested to achieve sediment EPS extraction. Extracted organic carbon amount and composition depend on the S/L ratio and method. Physical methods and CER extract mainly EPS, but in small quantities at S/L = 1/40. Chemical extractions give larger EPS amounts, but are not recommended. Chemical methods lead to contamination by salts, intracellular, and humic materials.